2009
DOI: 10.1017/s1368980008003923
|View full text |Cite
|
Sign up to set email alerts
|

Monetary cost of self-reported diet in relation to biomarker-based estimates of nutrient intake in young Japanese women

Abstract: Objective: All previous studies on monetary diet cost have examined the relationship of monetary cost of self-reported diet to self-reported, rather than biomarker-based, estimates of dietary intake. The present cross-sectional study examined the association between monetary costs of self-reported diet and biomarker-based estimates of nutrient intake. Design: Monetary diet cost (Japanese yen/1000 kJ) was calculated based on dietary intake information from a self-administered, comprehensive diet history questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…This condition raises the potential for correlated errors, which was recognized in earlier studies of diet and cost (45,46) and which, in our analysis, was mitigated in 2 ways: First, coefficients for calculating the AHEI score were both positive and negative (ie, certain foods increased scores, whereas others decreased them), although those for cost were all positive. As such, a correlation of errors would not necessarily exist, and if it did, it would tend to be low.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This condition raises the potential for correlated errors, which was recognized in earlier studies of diet and cost (45,46) and which, in our analysis, was mitigated in 2 ways: First, coefficients for calculating the AHEI score were both positive and negative (ie, certain foods increased scores, whereas others decreased them), although those for cost were all positive. As such, a correlation of errors would not necessarily exist, and if it did, it would tend to be low.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have investigated the relation between the healthfulness of diet and its cost by linking local or national food prices to food items reported on a questionnaire (2,3,6,11,45,48), diet record (5), 24-h recall (4), or face-to-face interview (4). Previous studies have also defined a healthful diet in a variety of ways: for example, in terms of adherence to a Mediterraneanstyle diet (6,14) or HEI (6) or as reflected by intake of select macro-and micronutrients (13).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Japan34 35 and Europe36–39 have shown that higher-cost diets are higher in nutritional quality34 36 38 39 and are associated with a lower body mass index 34 36 40. Fewer studies have examined food prices and diet cost in the context of socio-economic disparities in nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…17, 18, 19 More typically, diet costs are estimated by linking prices to diet history or food frequency questionnaires (FFQs). Following this approach, studies conducted in Europe, 12, 14, 20 the USA 11, 21, 22 and Japan 13, 23, 24 have produced diet cost estimates based on fixed tables of food prices containing 57–384 foods. However, costs estimated from FFQs might not be directly comparable to those obtained with diet diaries.…”
Section: Introductionmentioning
confidence: 99%